2010
DOI: 10.1186/1741-7015-8-51
|View full text |Cite
|
Sign up to set email alerts
|

Nightly treatment of primary insomnia with prolonged release melatonin for 6 months: a randomized placebo controlled trial on age and endogenous melatonin as predictors of efficacy and safety

Abstract: BackgroundMelatonin is extensively used in the USA in a non-regulated manner for sleep disorders. Prolonged release melatonin (PRM) is licensed in Europe and other countries for the short term treatment of primary insomnia in patients aged 55 years and over. However, a clear definition of the target patient population and well-controlled studies of long-term efficacy and safety are lacking. It is known that melatonin production declines with age. Some young insomnia patients also may have low melatonin levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 43 publications
(70 reference statements)
6
109
1
9
Order By: Relevance
“…Wade 146 found that the melatonin deficient group (including all ages) showed no improvement with melatonin versus placebo on SL at three weeks. However, the elder group (65-80 years) showed significant reduction of SL with melatonin, regardless of melatonin deficiency status (SL: −19.1 min; placebo −1.7 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wade 146 found that the melatonin deficient group (including all ages) showed no improvement with melatonin versus placebo on SL at three weeks. However, the elder group (65-80 years) showed significant reduction of SL with melatonin, regardless of melatonin deficiency status (SL: −19.1 min; placebo −1.7 min).…”
Section: Discussionmentioning
confidence: 99%
“…[141][142][143][144][145][146][147] These investigations employed various dosages and combinations with other agents, rendering meaningful comparisons to the 2 mg RCTs impossible. Pertinent features of these studies are included within each outcome section.…”
Section: Discussionmentioning
confidence: 99%
“…[84] Wade et al [48] preformed a trial over six months of daily melatonin use and demonstrated no adverse effects or rebound withdrawal symptoms. Two studies [62,85] that arise from sleep restriction (e.g., jet lag, shift-work), [4] but the results of their review may be partly attributable to trial limitations similar to those discussed in the current paper.…”
mentioning
confidence: 98%
“…Four trials studied the general adult population with pain [80][81][82][83][84] and three assessed the efficacy of CBT-I in older adults with pain. 79,85,86 McCurry is a second publication of an earlier trial analyzing only a portion of the participants with pain.…”
Section: Overview Of Studiesmentioning
confidence: 99%